PENYIDIKAN TINDAK PIDANA PENYALAHGUNAAN GAS ELPIJI BERSUBSIDI PADA SATUAN RESERSE KRIMINAL POLRES SAWAHLUNTO - Danu Aryadi (UNES Journal of Swara Justisia, 2020)
The crime of misuse of three kilogram LPG gas that occurred in the Sawahlunto district police jurisdiction, as in the police report LP/2/SPKT-A/2018/Res Swl, this crime includes the misuse of three kilogram LPG in the case of abuse in the field of supply and distribution . Although this matter has been regulated in the legislation namely Law No. 22 of 2001 concerning Oil and Gas, Minister of Energy and Mineral Resources Regulation No. 26 of 2009 concerning the Provision and Distribution of Liquefied Petroleum Gas, 3 Kilogram Republic of Indonesia Presidential Regulation Number 104 of 2007 concerning Provision, Distribution and Pricing of Liquefied Petroleum Gas 3 Kilograms. As for the unlawful act taking place in the Sawahlunto area, the law enforcement of the perpetrators of the abuse of the three kilogram LPG is handled by the Sawahlunto Regional Police Criminal Unit.